Pharmacology in clinical practice - Lancaster, Richard (Heinemann Medical Books, 1980)
Pharmacology in Clinical Practice describes basic pharmacology, clinical pharmacology, including the pharmacology of important drug groups. The author reviews the general principles of clinical pharmacology including drug actions, absorption, disposition, and excretion. Most drugs are xenobiotics-compounds foreign and harmful to human living tissues. Drugs should be properly metabolized and converted to nontoxic substance before being excreted either through spontaneous changes not mediated by enzymes or through transformation by enzyme systems. The author also discusses pharmacokinetics, incl.